Anterior Cruciate Ligament Injury and Knee Osteoarthritis: An Umbrella Systematic Review and Meta-analysis. Issue 2 (March 2022) - Webster, Kate E.; Hewett, Timothy E.
Abstract : Objective: To conduct a systematic review of reviews to summarize the (1) risk for development and (2) prevalence of knee osteoarthritis (OA) after anterior cruciate ligament (ACL) injury and surgical treatment and (3) compare prevalence rates between surgical and nonsurgical treatment of ACL injury. Date sources: Five electronic databases were searched using medical subject heading and text words up to February 2020 to identify English language reviews. Study selection: Studies were included if they were a systematic review or meta-analysis. Data extraction: Thirteen eligible reviews were included, and the main outcome extracted was knee OA prevalence or risk data and any meta-analysis results. Data synthesis: Results from reviews were combined with a summary meta-analysis based on odds ratios (ORs) or proportions. There was a near 7-fold and 8-fold increase in the odds for the development of knee OA post ACL injury [OR = 6.81 (5.70-8.13)] and ACL reconstruction [OR = 7.7, (6.05-9.79)]. Data were too heterogenous to specify a point estimate prevalence for OA after ACL injury, but OA prevalence was estimated at 36% (19.70-53.01) at near 10 years after reconstruction surgery. A significantly higher prevalence of OA was found for those who received surgical treatment at a minimum 10-year follow-up [OR = 1.40 (1.17-1.68)]. Conclusions: This study combines all data from previous systematic reviews into a single source to show that ACL injury markedly increases the risk for development of knee OA, which is likely to be present in the long term in approximately a third of patients who have reconstruction surgery. Surgical treatment does not reduce OA prevalence in the longer term compared with nonsurgical treatment. Abstract : Supplemental Digital Content is Available in the Text.